EVALUATION OF AIR QUALITY IN THE FINISHING WORKSHOP OF A TEXTILE INDUSTRY IN SANTA CLARA, CUBA - Rodríguez Berrio, Taila Elena; Román Iglesias, Daniela; Morales Pérez, Mayra Caridad; Álvarez Cruz, Arianna; Cabrera Estrada, Isabel (Centro Azúcar Journal, 2026)
Introduction: Air quality in the working environment of the textile industry that produces polypropylene bags is primarily affected by hygrothermal conditions, noise, particles from non-biodegradable fibers, and toxic gases. Objective: To evaluate the air quality in the finishing workshop of a textile industry in Santa Clara, Cuba. Materials and Methods: The methodology includes sampling of gases (NO₂, and SO₂), particles, and hygrothermal conditions using a sensor system from the company LIBELIUM, statistical post-processing of real-time monitoring, and calculation of CO₂ concentrations in the study area. Results and Discussion: The pollutants that deteriorate the working environment are SO₂, and NO₂, with daily average values exceeding the Maximum Allowable Concentrations (MAC) according to established standards, and temperature values affect thermal comfort of the working environment. Conclusions: The sampling conducted, which includes measurements of gas immission levels, particles, and hygrothermal conditions, allows for the diagnosis of air quality in the finishing workshop of this process.